5m+18=-5m-24-4m

Simple and best practice solution for 5m+18=-5m-24-4m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5m+18=-5m-24-4m equation:


Simplifying
5m + 18 = -5m + -24 + -4m

Reorder the terms:
18 + 5m = -5m + -24 + -4m

Reorder the terms:
18 + 5m = -24 + -5m + -4m

Combine like terms: -5m + -4m = -9m
18 + 5m = -24 + -9m

Solving
18 + 5m = -24 + -9m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '9m' to each side of the equation.
18 + 5m + 9m = -24 + -9m + 9m

Combine like terms: 5m + 9m = 14m
18 + 14m = -24 + -9m + 9m

Combine like terms: -9m + 9m = 0
18 + 14m = -24 + 0
18 + 14m = -24

Add '-18' to each side of the equation.
18 + -18 + 14m = -24 + -18

Combine like terms: 18 + -18 = 0
0 + 14m = -24 + -18
14m = -24 + -18

Combine like terms: -24 + -18 = -42
14m = -42

Divide each side by '14'.
m = -3

Simplifying
m = -3

See similar equations:

| 8ln(x+2.8)=12.8 | | 2(x)-3=11 | | -8(h+59)=-96 | | 4x+6=-3 | | 3(q-5)-2=4 | | 0.33ln(5-x)=0 | | (6-y)(6-y)=0 | | 7(5x+6)=18-(1x+6) | | 4(z-18)-20=-20 | | 37.4x=54.8 | | 6x+5x=7 | | 4(0.8x+15)=2(3+1.6x) | | 7x-8-2x=12 | | 4(h+2)+3=15 | | 5wx^2-2wx^2=3 | | 5=3(p+1)-1 | | ln(x-4)xln(x^2)=42 | | 12x+5=14x-21 | | (2q)=9-3q | | (2)q=9-3q | | 2x(2x-1)=3 | | 1-6x+5x=-6 | | -540+13.50=1500 | | 16=2(s-16)+8 | | 2-k=1 | | x(x-2)(x-6)=96 | | 15=3(d+1) | | 3n^2-2n+9=2 | | 4ab^2-3ab^2=1 | | 7n+3n-6n+2=18 | | (2)=(2)(b+(1)) | | (2x+24)+(4x-36)+6x=180 |

Equations solver categories